Collaborative translation: an instrument for commercial success or neutralizing a feminist message? - Kang, Ji Hae; Kim, Kyung Hye (Perspectives: Studies in Translation Theory and Practice, 2020)
This study examines the ways in which collaboration in audiovisual translation is approached and portrayed by different parties involved in the transnational distribution and consumption of cultural products. It considers the case of the Korean translation of Spy, an American action comedy spy film that was praised by many critics for its feminist message. Prior to its release in Korea, the film became widely known for its translators, which included a high-profile comedian, comedy scriptwriters, and a professional translator. Drawing on the concepts of ‘framing’ and ‘voice’, the present study shows how collaborative translation was used as a tool by the distributor to promote and market the film and to extend its commercial reach. The paper also argues that today’s viewers are not passive audiences. Empowered by social networks and digital devices, they actively share reviews and engage in discussions concerning translation method and quality, translators’ identities, and translation effects. Linking collaborative translation to what they see as the ‘flattening’ of a feminist voice and the insertion in the film of humor that reinforces unequal gender relations, many audiences actively resisted the distributor’s portrayal of collaborative translation as an optimal way to translate the film. The findings have implications for enhancing our understanding of collaborative translation work, translation of humor within the Korean cultural context, and perceptions on the connection between translation quality and collaborative translation.
Keywords: audiovisual translation (AVT); collaborative translation; film audience; framing; Subtitling